Familial periventricular nodular heterotopia, epilepsy and Melnick–Needles Syndrome caused by a single FLNA mutation with combined gain-of-function and loss-of-function effects. Issue 6 (9th March 2015) - Parrini, Elena; Mei, Davide; Pisanti, Maria Antonietta; Catarzi, Serena; Pucatti, Daniela; Bianchini, Claudia; Mascalchi, Mario; Bertini, Enrico; Morrone, Amelia; Cavaliere, Maria Luigia; Guerrini, Renzo
Abstract : Background: Loss-of-function mutations of the FLNA gene cause a neuronal migration disorder defined as X-linked periventricular nodular heterotopia (PNH); gain-of-function mutations are associated with a group of X-linked skeletal dysplasias designed as otopalatodigital (OPD) spectrum. We describe a family in which a woman and her three daughters exhibited a complex phenotype combining PNH, epilepsy and Melnick–Needles syndrome (MNS), a skeletal disorder assigned to the OPD spectrum. All four individuals harboured a novel non-conservative missense mutation in FLNA exon 3. Methods: In all affected family members, we performed mutation analysis of the FLNA gene, RT-PCR, ultradeep sequencing analysis in FLNA cDNAs and western blot in lymphocyte cells to further characterise the mutation. We also assessed the effects on RT-PCR products of treatment of patients' lymphocytes with cycloheximide, a nonsense mediated mRNA decay (NMD) inhibitor. Results: We identified a novel c.622G>C change in FLNA exon 3, leading to the substitution of a highly conserved aminoacid (p.Gly208Arg). Gel electrophoresis and ultradeep sequencing revealed the missense mutation as well as retention of intron 3. Cycloheximide treatment demonstrated that the aberrant mRNA transcript-retaining intron 3 is subjected to NMD. Western blot analysis confirmed reduced FLNA levels in lymphocyte cells. Conclusions: The novel c.622G>C substitution leads to two aberrant FLNA transcripts, one of which carries the missense mutation, plus a longer transcript resulting from intron 3 retention. We propose that the exceptional co-occurrence of PNH and MNS, two otherwise mutually exclusive allelic phenotypes, is the consequence of a single mutational event resulting in co-occurring gain-of-function and loss-of-function effects.